Survival Disparities Associated with Congenital Diaphragmatic Hernia. Issue 11 (10th April 2017) - Hinton, Cynthia F.; Siffel, Csaba; Correa, Adolfo; Shapira, Stuart K.
Abstract : Background: We assessed sociodemographic and clinical factors that are associated with survival among infants with congenital diaphragmatic hernia (CDH). Methods: Using data from the Metropolitan Atlanta Congenital Defects Program, we ascertained 150 infants born with CDH between 1979 and 2003 and followed via linkage with state vital records and the National Death Index. Kaplan–Meier survival probabilities and adjusted hazard ratios (HRs) were calculated for socioeconomic and clinical characteristics. Results: Survival increased from 40 to 62% over the study period. White infants born before 1988 were 2.9 times less likely to survive than those born after 1988. Black infants' survival did not show significant improvement after 1988. White infants' survival was not significantly affected by poverty, whereas black infants born in higher levels of poverty were 2.7 times less likely to survive than black infants born in lower levels of neighborhood poverty. White infants with multiple major birth defects were 2.6 times less likely to survive than those with CDH alone. The presence of multiple defects was not significantly associated with survival among black infants. Conclusions: Survival among infants and children with CDH has improved over time among whites, but not among blacks. Poverty is associated with lower survival among blacks, but not among whites. The presence of multiple defects is associated with lower survival among whites, but not among blacks. The differential effects of poverty and race should be taken into account when studying disparities in health outcomes. Birth Defects Research 109:816–823, 2017. © 2017 Wiley Periodicals, Inc.